Single cell transfection of human-induced pluripotent stem cells using a dropletbased microfluidic system - Pérez Sosa, Camilo José (2022)
Microfluidic tools have recently made possible many advances in biological and biomedical research. Research in fields such as physics, engineering, chemistry and biology have combined to produce innovation in microfluidics which has positively impacted diverse areas such as nucleotide sequencing, functional genomics, single-cell studies, single molecules assays and biomedical diagnostics. Among these areas, regenerative medicine and stem cells have benefited from microfluidics since these tools have had a profound impact on their applications. In this study, we present a high-performance droplet-based system for transfecting individual human-induced pluripotent stem cells. We will demonstrate that this system has great efficiency in single cells and captured droplets, like other microfluidic methods but with lower cost. Moreover, this microfluidic approach can be associated with the PiggyBac transposase-based system to increase its transfection efficiency. Our results provide a starting point for subsequent applications in more complex transfection systems, single-cell differentiation interactions, cell subpopulations and cell therapy, among other potential applications.